The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jssc.201800484
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acid hydrolysis, saponification and sample clean‐up on the measurement of phytosterols in dairy cattle feed using GC–MS and GC with flame ionization detection

Abstract: The fortification of processed foods including dairy products is increasingly commonplace with phytosterols among many compounds used to improve the nutritional value of food products. It is also increasingly common practice for some dairy cattle feeds to be fortified for their potential to increase phytosterol levels in milk. In this study, a combined, streamlined protocol using acid hydrolysis, saponification and sample clean-up was developed to enable the rapid and reliable measurement of phytosterols. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…Other plant sterols detected in the milk samples included campesterol and β-sitosterol but at minor or trace levels. In a recent study, the phytosterol content in the cattle feed used for this present study, lanosterol, and lathosterol were not detected (Duong et al, 2018). Given that both lanosterol and lathosterol were found in the milk, it suggested that their presence in milk was a result of endogenous synthesis.…”
Section: Overviewcontrasting
confidence: 46%
See 3 more Smart Citations
“…Other plant sterols detected in the milk samples included campesterol and β-sitosterol but at minor or trace levels. In a recent study, the phytosterol content in the cattle feed used for this present study, lanosterol, and lathosterol were not detected (Duong et al, 2018). Given that both lanosterol and lathosterol were found in the milk, it suggested that their presence in milk was a result of endogenous synthesis.…”
Section: Overviewcontrasting
confidence: 46%
“…It was observed that the mean lanosterol content was highest in the milk from the animals fed on the control diet and lowest in the milk from those feds on the DGM feed; however, this was not reflected in the cholesterol results for the different feed types. Examination of the phytosterol content in the respective diets showed that the control diet contained the lowest amount of phytosterols, with 4,254 mg compared with the WGM and DGM, which contained 9,922 mg (Duong et al, 2018). The results suggest that high phytosterol levels may affect the endogenous synthesis of lanosterol, because this is generally observed in human subjects ingesting a high plant sterol diet (Ostlund, 2002;Kritchevsky and Chen, 2005).…”
Section: Grape Marc Feeding Experimentsmentioning
confidence: 81%
See 2 more Smart Citations
“…However, through EC preparation, just PS in the free form are extracted. Indeed, various studies reported that the extraction of conjugated PS in food matrix requires a prior hydrolysis step in acidic conditions to break down ether and ester bonds linking PS in plant cell membranes [31,32].…”
Section: Extraction Of Ps In Ecmentioning
confidence: 99%